SINKRITISME, TASAMUH, DAN MODERASI: TANTANGAN SERTA PELUANG DALAM MEWUJUDKAN MASYARAKAT INKLUSIF - Malik, Hifdzul (STAI AL FALAH Banjarbaru, 2024)
AbstractMaintaining harmony among religious people is with an attitude of tolerance. Tolerance is not just about respecting each other. However, it is also about working together and helping in creating a harmonious atmosphere. As there is no religion that espouses hatred and violence, so it is important for us to refrain from prejudice and hatred. There are three concepts that can be used to maintain the harmony of syncretism, tsamuh, and moderation, of these three concepts are expected to be able to create an inclusive society.As for some of the challenges and opportunities in creating an inclusive society of the three concepts of syncretism, tsamuh, and moderation, among them the challenges to be faced are the misunderstanding between groups caused by lack of effective communication, the hegonomic factors of certain groups, and the negative impact of technological development and globalization. While the opportunities that can be taken are the level of public awareness related to living in harmony so that this can help in building good communication in the midst of differences, utilizing technology as a means of preaching and spreading the message of peace and tolerance. In creating an inclusive society requires cooperation and commitment from various parties. Keywords: Diversity, Openness, Social, Tolerance. AbstrakMenjaga keselarasan antar umat beragama adalah dengan sikap toleransi. Toleransi disini tidak sekedar menghormati satu sama lain. Namun, juga tentang bekerja sama dan membantu dalam menciptakan suasana yang harmonis. Seperti tidak adanya agama yang menganjarkan kebencian dan kekerasan, sehingga penting bagi kita untuk menahan diri dari prasangka dan kebencian. Ada tiga konsep yang dapat digunakan untuk menjaga keselarasan tersebut yaitu sinkritisme, tsamuh, dan moderasi, dari ketiga konsep ini diharapkannya mampu menciptakan masyarakat inklusif.Adapun beberapa tantangan dan peluang dalam menciptakan masyarakat inklusif dari tiga konsep sinkritisme, tsamuh, dan moderasi diantaranya tantangan yang akan dihadapi adalah dengan adanya kesalah pahaman antar kelompok yang disebabkan kurang efektifnya komunikasi, ada nya faktor hegonomi kelompok tertentu, dan dampak negatif dari perkembangan teknologi dan globalisasi. Sedangkan peluang yang dapat ditempuh adanya tingkat kesadaran masyarakat terkait hidup rukun sehingga ini mampu membantu dalam membangun komunikasi yang baik di tenggah-tenggah perbedaan, memanfaatkan teknologi sebagai sarana dakwah dan menebar pesan perdamaian dan toleransi. Dalam menciptakan masyarakat yang inklusif perlu kerjasama dan komitmen dari berbagai pihak. Kata Kunci: Keberagaman, Keterbukaan, Sosial, Toleransi.